Appraisal of the linkage among urban infrastructure and human resources and the growth of Information Technology (IT) industry in Indian cities. Issue 1 (31st December 2022) - Das, Dillip Kumar
Abstract: The Information Technology (IT) industry has significantly influenced the urban economy in many developing nations. Although the IT industry has created economic growth, it is argued that the establishment and growth of the IT industry depend on the availability of adequate urban infrastructures and human resources. Therefore, using data from Indian cities having significant IT industries, this study established the associations among various important urban infrastructures and human resources and the growth of the IT industry. A survey research method for data collection and statistical quantitative analyses and modelling were used for the study. The study revealed that houses, built-up spaces for offices and industry, urban roads and electrical power influence the growth of the IT industry considerably although in varying degrees. Houses and built-up space have a relatively higher influence than electrical power and roads. Human resources also influence fairly. The contributions of the study include the establishing of interlinkage among the urban infrastructures and human resources and the growth of the IT industry. Further, the consequent empirical models that emerged from the interlinkages will enable evaluation of the impact of infrastructure and human resources on the growth of the IT industry quantitatively, which could assist in developing policy options in the cities of developing countries such as India.